SELF-REGULATED LEARNING IN CORRELATION TO LEARNING OUTCOME OF COMPUTER-BASED TEST PREPARATION OF MEDICAL STUDENTS - Ade Pryta R. Simaremare (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: After the preclinical and clinical phase, medical students have to pass the Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) consisting the computer-based test (CBT) and objective structured clinical examination (OSCE). In preparation of the examinations, the student should follow tutoring activity. During the process, the student will be given try outs to measure the learning outcome. This study aimed to measure the self-regulated learning in correlation to learning outcome of Computer-based test of May 2018 batch preparation participants in Medan. Methods: This was an observational correlation analytic study with cross sectional method and 204 respondents collected. The self-regulated learning score obtained using a questionaire and the learning outcome obtained from the try out scores average gained by the respondents. Result: This study revealed that most of the participants represented bad in self-regulated learning (72,1%). The metacognition aspect mainly represented in bad (55,9%), the motivation aspect mainly represented in bad (77%), however, the behaviour aspect mainly represented in good (51,5%). The learning outcomes mainly represented in fail (87,3%). According to chi square test, this study showed that there was no correlation between self-regulated learning and learning outcome of students prepared for the CBT of May 2018 batch in Medan (p value = 0,731). Conclusion: Learning outcome affected by many factors. The students ability of learning, thinking, and problem solving affected by adaptation in values, beliefs, and customs that evolved in their social and cultural environment. Furthermore, it also affected by self confidence, motivation and learning purposes. Keywords: medical student, computer-based test, self-regulated learning, learning outcome